46, XX Infertile Male: A Case Report and Review in Infertility - Gito Restiansyah Wasian (Journal of Global Pharma Technology, 2016)
Introduction: 46, XX Testicular Disorder of Sex Development (46, XX Testicular DSD) is a genetic disorder that can cause male infertility. The clinical feature of this disorder varies, ranging from ambiguous genitalia to normal male genitalia characteristics. This disorder is rarely diagnosed early and is often only found during fertility tests. The objective of this work was to determine the characteristics and managements of patient with 46, XX testicular DSD. Methods: Case report and literature review. Results: A 30-year-old came with complaints of wanting to have children after a 7-year marriage. From physical examination, it was shown normal male external genitalia with small testicular volume. Sperm analysis showed azoospermia. From hormonal examination, hypogonadotropin hypogonadism is obtained. Cytogenetics gives an overview of 46, XX male with positive SRY gene. Conclusion: Patient characteristics vary depending on the mutation that occurs. Furthermore, 46, XX testicular DSD with can be found during holistic infertility examination, such as semen and hormonal analysis and karyotyping and SRY gene detection. A multidisciplinary approach should be performed too in the management, particularly for assisted reproductive technology with sperm donor or adoption.Keywords: 46, XX male, Testicular DSD, Male infertility, SRY gene.